The impact of the atmosphere on target archery - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Major target archery competitions are conducted outdoors and rarely pause due to inclement weather. The impact of the atmosphere on both the equipment and the archer is a very important consideration, affecting the arrow in free flight and the archer`s aim. This article provides a survey of research covering the arrow`s initial conditions as it enters its free flight phase, its behaviour during free flight including wind drift and the effects of wind on the archer`s aim. Potential areas for further investigation are highlighted.